ANALISIS KUALITAS LAYANAN, KEPERCAYAAN, DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN - Dicky Iksar Wahyujati, 11.05.51.0010; Marlien, R.A (Students' Journal of Economic and Management, 2017)
This research was conducted in Bread Brownies Maylisa caused due to a phenomenon that occurs in terms of revenue earned Roti Brownies Maylisa from 2013 until 2015 which is not in accordance with the target set by management Bread Brownies Maylisa. The aim of research to analyze the influence of service quality, trust and brand image on customer loyalty and customer satisfaction as a mediating variable.Sample of 100 respondents / customers Roti Brownies Maylisa. The sampling technique used was purposive sampling technique of data collection was done by distributing questionnaires to customers Roti Brownies Maylisa with consideration or the following criteria: (1) customer aged 17 years and above, and (2) at least never bought Roti Brownies Maylisa by 5 time. Methods of data analysis using linear regression.The test results showed that there are significant partial positive and significant correlation between quality of service, trust and brand image on customer satisfaction. Other results showed partially not there are positive influence between quality of service and brand image of the customer loyalty. Partially there are significant positive and significant correlation between confidence and satisfaction on customer loyalty. The test results demonstrate the mediating effect of satisfaction were able to mediate the effect of service quality on customer loyalty, satisfaction does not mediate the effect of trust on customer loyalty and satisfaction does not mediate the effect of brand image on customer loyalty. Keywords: quality of service, trust, brand image, customer satisfaction and customer loyalty